CLEANING VALIDATION OF A MULTIPURPOSE TANK USED FOR TYPE B HAEMOPHILUS INFLUENZAE AND MENINGITIS A AND C VACCINE FORMULATION: Pharmaceutical-Analytical chemistry - CHRISTINA BAGO, BARBARA; DOLAVALE, LEIDIANE; SEVERINO LUNA, ADERVAL; CARLOS AUGUSTO DA COSTA, ANTONIO (International Journal of Life Science and Pharma Research, 2012)
The cleaning procedure of a multipurpose tank was validated to ensure the proper removal of waste products and cleaning agents according to regulatory requirements that define acceptable contamination and crosscontamination levels. The analytical methodology chosen to monitor the level of contamination was the measurement of total organic carbon content (TOC); this is a non-specific technique that allows the quantification of organic residues before and after the cleaning procedure. To complete this cleaning validation, a worst case scenario for the contaminant was selected, and the strictest criteria were followed in order to demonstrate cleanliness. Residue recovery tests were performed using swabs and also by rinsing water on specific sampling positions. The results show that the cleaning procedure for this 316 L stainless steel tank was effective in the removal of Haemophilus influenzae type B and Meningitis A and C vaccines residues to acceptable levels. Furthermore, the undetectable levels of the sanitizing solution used for cleaning the shared tank, which is used to formulate both vaccines, supports the possibility of using the same reactor to formulate both vaccines without cross-contamination.